Impact of acute kidney injury on anticancer treatment dosage and long-term outcomes: a pooled analysis of European Organisation for Research and Treatment of Cancer trials - Péron, Julien; Neven, Anouk; Collette, Laurence; Launay-Vacher, Vincent; Sprangers, Ben; Marreaud, Sandrine (Nephrology, dialysis, transplantation, 2021)
The impact of kidney dysfunction on long-term outcomes of patients with advanced cancer remains unclear. Patients with advanced cancer included in trials conducted by the European Organisation for Research and Treatment of Cancer were eligible for this retrospective analysis. Acute kidney injury (AKI) was identified using serum creatinine levels and using adverse events reported by investigators. The impact of baseline estimated glomerular filtration rates (eGFRs) on progression-free survival (PFS) and overall survival (OS) was investigated. Pooled estimates of the impact of AKI on dose intensity, treatment duration, PFS and OS were obtained following a meta-analytic process. Nine trials were included in this study, totalling 2872 metastatic patients with various tumour types and various systemic treatment types. Baseline eGFR had homogeneously no impact on PFS or OS. Most Risk, Injury, Failure, Loss of kidney function and End-stage kidney disease (RIFLE) events occurred early during the course of the treatment. AKI was not associated with an increased rate of treatment discontinuation, while it decreased the study treatment dose intensity. Occurrence of a first RIFLE event significantly and homogeneously reduced PFS (pooled hazard ratio = 1.18, 95% confidence interval 1.07-1.30; P = 0.0012), while its impact on OS was more heterogeneous across trials. AKI is associated with reduced treatment dose intensity and reduced PFS. Therefore, close monitoring of the kidney function during the first months of treatment should be included in clinical trial protocols and probably also in daily practice to enable early AKI diagnosis and management. Collaboration between oncologists and nephrologists is needed to reduce the risk of undertreatment of patients experiencing AKI.